Cerebrovascular Reactivity: Purpose, Optimizing Methods, and Limitations to Interpretation – A Personal 20-Year Odyssey of (Re)searching - Fisher, Joseph A.; Mikulis, David J. (Frontiers in Physiology, 2021)
The brain is a neurovascular organ. A stimulus-response approach is effective in interrogating the physiology of its vasculature. Ideally, the stimulus is standardized across patients, and in a single patient over time. We developed a standard stimulus and attempted to measure, classify and interpret the many forms of responses. Over the past 20 years our work has delivered nuanced insights into normal cerebral vascular physiology, as well as adaptive physiological responses in the presence of disease. The trajectory of our understanding did not follow a logical linear progression; rather it emerged as a coalescence of new, old, and previously dismissed, ideas that had accumulated over time. In this essay, we review what we believe were our most valuable—and sometimes controversial, insights during our decades-long journey.